Shrek forever after [videorecording (DVD)] : the final chapter - Mitchell, Mike (Director); Diaz, Cameron; Banderas, Antonio; Murphy, Eddie, 1961-; Andrews, Julie; Myers, Mike, 1963-; Steig, William, 1907-2003 (DreamWorks Home Entertainment, 2010)
Longing for the days when he was a 'real ogre,' Shrek signs a deal with Rumpelstiltskin to get his roar back, but turns his world upside down in the process. Donkey suddenly can't remember his best friend, Fiona is now a tough warrior princess, and Puss in Boots is one fat cat! Together, they have just 24 hours to reverse the contract and restore happily forever after.